Prevalence of hepatitis B and hepatitis C virus infection in humans of Mymensingh, Bangladesh - Rudra, S; Chakraborty, P; Poddar, B (Mymensingh Medical Journal, 2011)
Mymensingh Med J. 2011 Apr;20(2):183-6. The abstract of this article is available on the PubMed website